2015
DOI: 10.14807/ijmp.v6i3.315
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Innovation in the Competitiveness of Brazilian Organic Products

Abstract: This research aimed at identifying the influence of the innovation in the competitiveness of organic agriculture and food industries in Brazil, seeking to create adhesion between a review of the literature and an empirical research about the strategies for innovation and competitiveness in the area. The trend in the globalized market indicates favorable prospects for organic food industries and, for this reason, they have realized the need for restructuration in order to meet the demands. The food industry has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“… 2008 ; Beuchelt and Zeller 2013 ) and innovative capacity (Chikán 2008 ; Delfin-Ortega and Valencia 2015 ; Miniussi et al. 2015 ; Díaz-Chao et al. 2016 ) variables were reported as factors positively affecting competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“… 2008 ; Beuchelt and Zeller 2013 ) and innovative capacity (Chikán 2008 ; Delfin-Ortega and Valencia 2015 ; Miniussi et al. 2015 ; Díaz-Chao et al. 2016 ) variables were reported as factors positively affecting competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Followers Miniussi et al (2015) revealed the impact of innovation on the competitiveness of the organic agricultural state and food industry in Brazil, evaluating the link between strategic innovation and competitiveness in this area. Abraham et al (2015) identified factors that contribute to the competitiveness of Czech small and medium-sized enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…http://www.ijmp.jor.br v. 10, n. 3, May -June 2019 ISSN: 2236-269X DOI: 10.14807/ijmp.v10i3.843 fertilizers and synthetic pesticides, are not allowed according to Miniussi, Coti-Zelati and Araújo (2015). These authors see organic agriculture as several intersecting streams of lines of research and thought.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%